Selenium Deficiency Leads to Inflammation, Autophagy, Endoplasmic Reticulum Stress, Apoptosis and Contraction Abnormalities via Affecting Intestinal Flora in Intestinal Smooth Muscle of Mice - Wang, Fuhan; Sun, Ni; Zeng, Hanqin; Gao, Yuan; Zhang, Naisheng; Zhang, Wenlong (Frontiers in Immunology, 2022)
Selenium (Se) is a micronutrient that plays a predominant role in various physiological processes in humans and animals. Long-term lack of Se will lead to many metabolic diseases. Studies have found that chronic Se deficiency can cause chronic diarrhea. The gut flora is closely related to the health of the body. Changes in environmental factors can cause changes in the intestinal flora. Our study found that Se deficiency can disrupt intestinal flora. Through 16s high-throughput sequencing analysis of small intestinal contents of mice, we found that compared with CSe group, the abundance of Lactobacillus, Bifidobacterium, and Ileibacterium in the low selenium group was significantly increased, while Romboutsia abundance was significantly decreased. Histological analysis showed that compared with CSe group, the small intestine tissues of the LSe group had obvious pathological changes. We examined mRNA expression levels in the small intestine associated with inflammation, autophagy, endoplasmic reticulum stress, apoptosis, tight junctions, and smooth muscle contraction. The mRNA levels of NF-κB, IκB, p38, IL-1β, TNF-α, Beclin, ATG7, ATG5, LC3α, BaK, Pum, Caspase-3, RIP1, RIPK3, PERK, IRE1, elF2α, GRP78, CHOP2, ZO-1, ZO-2, Occludin, E-cadherin, CaM, MLC, MLCK, Rho, and RhoA in the LSe group were significantly increased. The mRNA levels of IL-10, p62 BcL-2 and BcL-w were significantly decreased in the LSe group compared with the CSe group. These results suggest that changes in the abundance of Lactobacillus, bifidobacterium, ileum, and Romboutsia may be associated with cellular inflammation, autophagy, endoplasmic reticulum stress, apoptosis, tight junction, and abnormal smooth muscle contraction. Intestinal flora may play an important role in chronic diarrhea caused by selenium deficiency.